Pengaruh Self Hypnosis Terhadap Penurunan Kecemasan Pada Ibu Hamil Trimester III Dalam Menghadapi Persalinan - Eliyawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2024)
Nowadays, many researchers are conducting research using various methods to reduce anxiety and discomfort in pregnant women using non-pharmacological methods, namely by providing self-hypnosis therapy. The aim of the research is to determine the effect of self-hypnosis on reducing anxiety levels in third trimester pregnant women facing childbirth at Abdoer Rahem Hospital in 2024. This research method uses quasi-experiment, with one group pretest posttest. The population of this study was 40 pregnant women in the third trimester at Abdoer Rahem Hospital, Situbondo. The sample for this study was 40 people using the total sampling method with 20 people in the control group and 20 people in the intervention group. Data were collected using an observation sheet or checklist and analyzed univariately and bivariately using the Wilcoxsion test and presented in the form of a frequency distribution table. The results of this study have a p-value of 0.000 < α 0.05, so it can be concluded that there is an effect of providing self-hypnosis therapy on reducing anxiety levels in pregnant women in the third trimester before giving birth at Abdoer Rahem Hospital, Situbondo. Researchers hope that this research can be used as a reference for pregnant women in reducing anxiety with self-hypnosis therapy. To have a happy, calm and peaceful pregnancy before delivery.